Ultrasound assessment of muscle thickness and muscle crosssectional area: a reliability study - Nijholt, W. (2016)
Purpose: Previous studies showed that ultrasound imaging is reliable when measuring the cross-sectional area (CSA) of a muscle. However, measurements of muscles could be affected by the level of experience of the observer. The aim of this pilot study was to investigate the reliability of observers when measuring the CSA and thickness of the rectus femoris (RF). Methods and Materials: Seven observers assessed eight different images of RF. On each image, the CSA and thickness were measured three times using ImageJ. The measurements were analyzed using IBM SPSS. Intraclass Correlation Coefficient (ICC) and Bland-Altman plots were used to analyze reliability. A Paired Sample T-Test was used to investigate any differences between the first and mean measurement recorded by the observers. Results: No significant differences were found between the first and mean of the repeated measures for CSA and thickness respectively (p = 0.217-0.817, p = 0.337-0.897). Intra-observer reliability shows excellent agreement between measurement one and the mean for each observer (CSA ICC = 0.987-1.000, thickness ICC = 0.996-1.000). High inter-observer reliability was found for both CSA (ICC = 0.938, 95% CI = 0.845-0.985) and thickness (ICC = 0.9774, 95% CI = 0.934-0.994). Agreement between an experienced and inexperienced observer was excellent (ICC = 0.991, 95% CI = 0.959-0.998). Conclusion: This pilot study shows that there is a high level of inter- and intraobserver reliability among the observers in measuring the CSA and thickness of the RF. It also shows that experience in ultrasound measurements is not a factor in reliability.